2022
DOI: 10.3324/haematol.2022.280603
|View full text |Cite
|
Sign up to set email alerts
|

The successful use of eculizumab for treatment of thrombotic microangiopathy in pediatric acute SARSCoV2 infection and multisystem inflammatory syndrome in children

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Studies describing the plasma and serum proteomic analysis revealed that many complement components and their regulators were significantly upregulated in adult patients with COVID-19. 18,[39][40][41][42] Diorio et al 24 observed that soluble C5b-9, 13,22 MBL pathway, C3, and C4 levels were elevated in children with SARS-CoV-2 infection, 43 and complement-mediated thrombotic microangiopathy (TMA) has been associated with SARS-CoV-2 infection. 23 A 2022 study 44 determined that the MIS-C group exhibited increased frequencies of the complement factor H coding single nucleotide variants potentially predisposing to complement deregulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies describing the plasma and serum proteomic analysis revealed that many complement components and their regulators were significantly upregulated in adult patients with COVID-19. 18,[39][40][41][42] Diorio et al 24 observed that soluble C5b-9, 13,22 MBL pathway, C3, and C4 levels were elevated in children with SARS-CoV-2 infection, 43 and complement-mediated thrombotic microangiopathy (TMA) has been associated with SARS-CoV-2 infection. 23 A 2022 study 44 determined that the MIS-C group exhibited increased frequencies of the complement factor H coding single nucleotide variants potentially predisposing to complement deregulation.…”
Section: Discussionmentioning
confidence: 99%
“…53 It has been previously found that the levels C3 and C5 levels were elevated in severe COVID-19 adult patients. 54 Diorio et al 24 observed that soluble C5b-9, 13,22 complement activation and complement-mediated thrombotic microangiopathy (TMA) have been associated with SARS-CoV-2 infection. 23 In our cohort of children, we found that the levels of C3 and C5a levels were elevated in children with MIS-C and acute COVID-19, which suggests that prolonged and excessive activation in the host may be what leads to pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, patients with severe COVID-19 caused by SARS-CoV-2 have severe tissue damage attributed to increased complement activity ( 65 ). One small case series described the successful use of eculizumab in pediatric acute SARS-CoV2 infection, multisystem inflammatory syndrome and thrombotic microangiopathy ( 66 ). The same principle of complement inhibition has been tested in a small phase-II clinical trial of adult patients with severe COVID-19 caused by SARS-CoV-2.…”
Section: Complement Deficiencymentioning
confidence: 99%